Pilot Study on Folate Bioavailability from a Camembert Cheese Reveals Contradictory Findings to Recent Results from a Human Short-term Study - Mönch, Sabine; Netzel, Michael; Netzel, Gabriele; Ott, Undine; Frank, Thomas; Rychlik, Michael (Frontiers in Nutrition, 2016)
Different dietary sources of folate have differing bioavailabilities which may affect their nutritional “value”. In order to examine if these differences also occur within the same food products, a short term human pilot study was undertaken as a follow-up study to a previously published human trial to evaluate the relative native folate bioavailabilities from low-fat Camembert cheese compared to pteroylmonoglutamic acid as the reference dose. Two healthy human subjects received the test foods in a randomized cross-over design separated by a 14-day equilibrium phase. Folate body pools were saturated with a pteroylmonoglutamic acid supplement before the first testing and between the testings. Folates in test foods and blood plasma were analysed by stable isotope dilution assays. The biokinetic parameters Cmax, tmax and AUC were determined in plasma within the interval of 0 to 12 hours. When comparing the ratio estimates of AUC and Cmax for the different Camembert cheeses, a higher bioavailability was found for the low-fat Camembert assessed in the present study (≥64%) compared to a different brand in our previous investigation (8.8%). It is suggested that these differences may arise from the different folate distribution in the soft dough and firm rind as well as differing individual folate vitamer proportions. The results clearly underline the importance of the food matrix, even within the same type of food product, in terms of folate bioavailability. Moreover, our findings add to the increasing number of studies questioning the general assumption of 50 % bioavailability as the rationale behind the definition of folate equivalents. However, more research is needed to better understand the interactions between individual folate vitamers and other food components and the potential impact on folate bioavailability and metabolism.